Deciphering the drivers of CO2 emissions in Haryana: a comprehensive analysis from 2005 to 2023 - Kumar, Parveen; Fatima, Nudrat; Khan, Muhammad Kamran; Alnafisah, Hind (Frontiers in Environmental Science, 2025)
This study investigates the key factors influencing CO2 emissions in the state of Haryana from 2005 to 2023, focusing on economic and demographic determinants. Understanding the relationship between economic growth, population dynamics, and environmental impact is crucial for formulating effective sustainable development policies. The study employs a comprehensive dataset where CO2 emissions serve as the dependent variable, while Net State Domestic Product (NSDP) at constant prices, the square of NSDP, population growth, and life expectancy act as independent variables. To ensure robust analysis, stationarity tests are conducted to assess the data properties, followed by Dynamic Ordinary Least Squares (DOLS) and Canonical Cointegration Regression to explore long-run relationships among these variables. Empirical findings indicate a positive and statistically significant relationship between CO2 emissions, NSDP, and population growth, suggesting that economic expansion and population increase drive higher emissions. Conversely, life expectancy exhibits a negative association with CO2 emissions, implying that improvements in public health and longevity may contribute to reduced emissions. The results highlight the environmental challenges posed by economic and demographic growth, emphasizing the need for balanced policy measures that align economic progress with sustainability goals. The unexpected negative relationship between life expectancy and emissions underscores the complex interplay between socioeconomic development and environmental sustainability, warranting further investigation.